Empathy and stress: the mediating impact of the emotional labor strategies on the example of surgical nurses - Maciej Załuski; Paweł Jagielski; Marta Makara-Studzińska (Nofer Institute of Occupational Medicine, 2020)
Background The nurse, when performing emotional labor at work, tunes her own emotions to the patient's expectations. The self-regulation strategies which are then used weaken her mental strength and contribute to various symptoms of occupational burnout syndrome (OBS). In addition, certain positive relationships have been found between selected emotional labor strategies and increased work engagement. The skills of empathizing with the patient are the nurse's protective resource. Empathy allows to share emotions with the patient while maintaining the attitude of a neutral observer. It also helps to take actions to reduce pain and suffering, and to build a relationship of mutual trust and cooperation. The purpose of the present study, conducted in a group of surgical nurses in January‒March 2019, was to analyze a theoretical model which assumed the mediating role of emotional labor strategies in the relationship between empathy and OBS. Material and Methods The sample consisted of 84 surgical nurses employed at the University Hospital in Kraków. A cross-sectional design was used with the application of a questionnaire method. In the study, the Polish version of the Link Burnout Questionnaire by Jaworowska was used, together with the Empathy Quotient - short by Jankowiak-Siuda and the Deep Acting and Surface Acting Scale by Finogenow. For the statistical analysis, the IMB SPSS Statistics 24 with Hayes PROCESS version 3.4 was employed. Results A negative correlation between the level of empathy and the severity of OBS symptoms was confirmed in the study. The use of the surface regulation strategies of emotional labor weakened the protective effect of empathy on burnout. The use of deep action processing strategies of emotional labor supported this relationship. Conclusions The flexible use of emotional self-regulation strategies by the medical staff deepens their personal contact with the patient, and mediates in the level of empathy and the severity of OBS symptoms. Med Pr. 2020;71(4):461-71